Atrocity, Punishment, and International Law - Drumbl, Mark A (Cambridge University Press, 2013)
Howdo we, and howshould we, punish someone whocommits genocide, crimes against humanity, or discrimination-based war crimes? These questions – the former descriptive, the latter normative – are the focus of this book. These questions have received much less attention than they deserve. Although international criminal law has gone a long way to convict individuals for perpetrating atrocity, it has traversed far less creative ground in terms of conceptualizing how to sanction them. Scholars, too, have been remiss. Surprisingly little work has been undertaken that explores how and why criminal justice institutions punish atrocity crimes and whether the sentences levied by these institutions actually attain the proffered rationales. Furthermore, there is little empirical work that assesses whether what international tribunals doctrinally say they are doing actually has a consistent and predictable effect on the quantum of sentence